Digitalization and post-pandemic recovery of micro-businesses in Colombia (2024)
This research paper investigates the correlation between the extent of digitalization and business recovery in microenterprises in Colombia one year after the start of the 2019 Coronavirus (COVID-19). The study involved the analysis of 1.600 surveys conducted across various sectors of microenterprises. The findings revealed that, on average, businesses that had embraced a higher degree of digitization demonstrated a more significant rebound in their sales following the constraints imposed by the pandemic.